A PROPOSED SECURITY ARCHITECTURE FOR ESTABLISHING PRIVACY DOMAINS IN E-HEALTH CLOUD - Z., Al-Khanjari; A., Al-Ani; S., Al-Hermizy (European Scientific Journal, ESJ, 2014)
Information and communication technology (ICT) are becoming a natural part in healthcare. Instead of keeping patient information inside a written file, you can find all information stored in an organized database as well defined files using a specific system in almost every hospital. But those files sometimes got lost or information was split up in files in different hospitals or different departments so no one could see the whole picture from this point we come up with our idea. One of this paper targets is to keep that information available on the cloud so doctors and nurses can have an access to patient record everywhere, so patient history will be clear which helps doctors in giving the right decision. We present security architecture for establishing privacy domains in e-Health bases. In this case, we will improve the availability of medical data and provide the ability for patients to moderate their medical data. Moreover, e-Health system in cloud computing has more than one component to be attacked. The other target of this paper is to distinguish between different kinds of attackers and we point out several shortcomings of current e-Health solutions and standards, particularly they do not address the client platform security, which is a crucial aspect for the overall security of e-Health systems. To fill this gap, we present security architecture for establishing privacy domains in e-Health infrastructures. Our solution provides client platform security and appropriately combines this with network security concepts.